Analisis Kepemimpinan Kepala Desa Dalam Meningkatkan Kepuasan Kerja Pegawai Di Desa Raksajaya - Mawarni, Ica; Dwi Marselina, Resya (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to analyze leadership at the Raksajaya Village office, Sodonghilir subdistrict, Tasikmalaya Regency, West Java Province, using a qualitative approach. Using the descriptive analysis method, data collection was carried out through observation, interviews and documentation studies. The results of this research show that the leadership at the Raksajaya Village office can be said to be quite good. However, there are still several aspects that need to be improved, such as more open communication, a fairer compensation system. It is hoped that with improvements in these aspects, employee job satisfaction can increase.